Development of a layered bacterial nanocellulose‐PHBV composite for food packaging. (14th March 2022) - A G Soares da Silva, Francisco; Matos, Mariana; Dourado, Fernando; A M Reis, Maria; C Branco, Pedro; Poças, Fátima; Gama, Miguel
Abstract: BACKGROUND: Most of the current materials used in food packaging are synthetic and non‐degradable, raising environmental issues derived from the accumulation of plastics in landfills/waterways. The food industry increasingly needs eco‐friendly sustainable materials that meet food‐packaging requirements. Bacterial nanocellulose (BNC), a biopolymer obtained by fermentation, offers very good mechanical properties and the ability to carry and deliver active substances. However, its water‐vapor permeability is too high for food‐packaging applications. In this work, a layered biodegradable composite based on BNC and polyhydroxyalkanoate (PHBV) was produced, attempting to improve its overall barrier properties. Polyhydroxyalkanoate is a biopolymer with high degree of hydrophobicity and biodegradability, and is also obtained by fermentation. Wet BNC membranes produced by static culture were plasticized by impregnation of solutions of either glycerol (BNCgly ) or polyethylene glycol (MW 600) (BNCPEG ). The plasticized BNC was then coated with PHBV solution dissolved in formic acid, and oven dried at 148 °C. RESULTS: Overall, PHBV coating on plasticized BNC reduced water vapor permeability significantly (from 0.990 to 0.032 g.μm.m −2 .day −1 .Pa −1 ) under 50% relative humidity. It increased the hydrophobicity (contact angle from 10–40° to 80–90°) but decreased the stiffness (from 3.1 GPa to 1.3 Gpa) of the composite. CONCLUSIONS: Overall, the mechanical and barrier properties of the layered composite obtained were considered suitable for food‐packaging applications. The plasticizing (with glycerol or polyethylene glycol) of BNC significantly improved the mechanical performance and the PHBV coating reduced the water affinity (vapor and liquid state) on BNC. © 2022 Society of Chemical Industry.